Pendampingan Budidaya Sayur di Kelompok Wanita Tani (KWT) Lestari Dusun Dadapbong, Sendangsari - Pramesthi, Meriska Indamaris; Qorib, Mukhammad Fatkhul; Rahmawati, Nabila Cantika; Triyadi, Gunawan; Wardhani, Stephanie Devty Sekar Anggitya; Evita, Vidya; Nabila, Jihan; Kristyaji, Muhammad Ro'iyan; Khaleda, Najmi; Annafi, Mufti Haiza Mahira; Ibrahim, Abdihakin Mohamoud; Azzahra, Syifa Noriza; Al-Obadi, Tareq Mohammed Ali; Widodo, Aris Slamet (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Farmer groups play a crucial role in driving agricultural development in rural areas. Their role as key actors in agricultural development includes ensuring the availability of essential agricultural inputs (fertilizers, soil, and irrigation water), providing access to information through counseling, and facilitating the collective marketing of harvests. One of the challenges in developing KWT Lestari in Padukuhan Dadapbong is the lack of access to education and training for its members. This issue can arise due to various factors, such as remote geographical locations, difficulties in controlling crop pests due to a lack of knowledge about effective pest management techniques, especially when cultivating plants in dry soil conditions during the dry season, which often leads to crop failure and low agricultural productivity. The purpose of this community service program is to enhance the knowledge and skills of KWT Lestari members regarding effective and sustainable vegetable cultivation techniques and to provide insights into suitable plant varieties based on soil conditions and the local climate. The methods used in this program include needs assessment through Forum Group Discussions (FGD) and interviews, counseling, training, and mentoring. The results of the activities showed a significant improvement in the understanding and skills of KWT Lestari members in vegetable cultivation. The counseling sessions provided new insights into marketing strategies, enabling them to better manage their harvests and increase the market value of agricultural products. This program contributes to the development of agricultural enterprises, strengthens local food security, and improves community welfare. It also proves that a community-based approach, supported by academics, can be an effective solution in empowering farmer groups in rural areas